Advances in Transdermal Drug Delivery: The Development of Microneedle Technology for Improved Therapeutic Outcomes - Nagrik, Shivshankar M.; Akhare , Vaishnavi S.; Bhade , Manisha W.; Nayse , Mohini R.; Gulhane, Ankita G.; Bhorkhade , Shreya P.; Nagrik, Shatrughna U.; Verulkar , Ashwini G. (Journal for Research in Applied Sciences and Biotechnology, 2024)
Transdermal Drug Delivery Systems (TDDS) represent a significant advancement in therapeutic administration by allowing drugs to bypass the gastrointestinal system and first-pass hepatic metabolism, enhancing patient compliance, and enabling sustained drug release. However, traditional TDDS face limitations, including resistance from the skin's natural barrier and limited efficacy in delivering large or hydrophilic molecules. Microneedle (MN) technology offers a breakthrough solution, using minimally invasive micron-sized needles to bypass the stratum corneum, facilitating efficient drug delivery without significant pain or discomfort. This review explores the evolution and recent advancements in microneedle technology, highlighting its role in overcoming the limitations of conventional TDDS. Microneedles have been shown to enhance drug bioavailability, reduce side effects, and expand the range of deliverable therapeutics, including vaccines, insulin, and genetic materials. The development of bioinspired 4D microneedles further extends their application to diagnostics and cosmetic treatments, positioning MNs as a versatile tool in modern medicine. Key sections of the review focus on the types of microneedles—solid, coated, dissolving, hollow, and hydrogel-forming—and their respective fabrication methods, materials, and drug delivery mechanisms. The review also discusses the challenges related to scaling up production, ensuring consistent quality, and regulatory hurdles in achieving clinical approval. Future directions include the integration of microneedles with nanotechnology, combination therapies, and sustainable design, particularly in developing regions where biodegradable materials may address environmental and disposal concerns. The potential for microneedle technology to revolutionize transdermal drug delivery, diagnostics, and therapeutic monitoring is significant, with ongoing research paving the way for multifunctional applications that can reshape patient care and treatment modalities.